Design and Construction of a NLP Based Knowledge Extraction Methodology in the Medical Domain Applied to Clinical Information - Denis Cedeño Moreno; Miguel Vargas-Lombardo (Healthcare Informatics Research, 2018)
ObjectivesThis research presents the design and development of a software architecture using natural language processing tools and the use of an ontology of knowledge as a knowledge base.MethodsThe software extracts, manages and represents the knowledge of a text in natural language. A corpus of more than 200 medical domain documents from the general medicine and palliative care areas was validated, demonstrating relevant knowledge elements for physicians.ResultsIndicators for precision, recall and F-measure were applied. An ontology was created called the knowledge elements of the medical domain to manipulate patient information, which can be read or accessed from any other software platform.ConclusionsThe developed software architecture extracts the medical knowledge of the clinical histories of patients from two different corpora. The architecture was validated using the metrics of information extraction systems.